2016
DOI: 10.1016/j.jcin.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Robotic Peripheral Vascular Interventions

Abstract: These data demonstrate the feasibility and safety of using a robotic-assisted platform for performing peripheral arterial revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…The evidence demonstrating the efficacy of robotically assisted revascularization is growing. This platform has now been shown to be safe and feasible for use in complex high‐risk interventions, left main interventions, and peripheral interventions including above and below the knee interventions . Further research in a larger patient cohort may provide insight into the safety and effectiveness of the combined robotic and laser atherectomy platform for routine use in complex coronary interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence demonstrating the efficacy of robotically assisted revascularization is growing. This platform has now been shown to be safe and feasible for use in complex high‐risk interventions, left main interventions, and peripheral interventions including above and below the knee interventions . Further research in a larger patient cohort may provide insight into the safety and effectiveness of the combined robotic and laser atherectomy platform for routine use in complex coronary interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility, safety, and high technical success of robotically assisted percutaneous coronary intervention (PCI) for the treatment of both simple and complex coronary disease including left main PCI has been demonstrated, with patient and procedural outcomes comparable to manual PCI . The robotic platform has also been shown to be safe and feasible for use in peripheral arterial disease interventions . The CorPath GRX Vascular Robotic System (Corindus, Waltham, MA) is a second generation robotically assisted PCI system, designed for remote control of coronary guide catheters, guidewires, and balloon/stent catheters during PCI procedures (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…The RAPID (Robotic‐Assisted Peripheral Interventions for Peripheral Artery Disease) trial, a prospective single center, safety and feasibility study demonstrated the utility of the CorPath 200 system for robotic PVI. Patients with symptomatic PAD affecting the femoro‐popliteal artery due to either lifestyle limiting claudication or critical limb ischemia requiring PVI were enrolled . The objective of this study was to examine the CorPath 200 performance at delivering guidewires and balloons to the identified lesions.…”
Section: The Systemsmentioning
confidence: 99%
“…Lastly, the robotic‐assisted PCI system has demonstrated success with peripheral artery disease (PAD) . In the RAPID trial, Mahmud et al investigated the CorPath 200 system in 20 patients with Rutherford class 3–5 PAD involving the femoropopliteal artery.…”
Section: Outcomes Of the Robotic‐assisted Pci Systemmentioning
confidence: 99%